Application technology with the use of different adjuvants in soybean culture - Rosa, David Peres da; Pegoraro, Anderson; Girardi, Junior Santana; Santos, Taciane dos; Spagnollo, Roger Toscan (Revista de Ciências Agroveterinárias, 2022)
The objective of this work has been to evaluate the efficiency of the effect of the addition of four types of adjuvants in the spray solution used in the soybean (Glycine max L.) crop. The experimental design was the randomized blocks with five treatments based on the application of adjuvants, as follows: without adjuvant (control) and with the adjuvants Blend®, Tech-Plus®, LI700®, and Protect®. For qualification, the number of droplets, relative dispersion, volume median diameter, volume applied to the target, droplet density, and percentage of coverage in the upper, middle, and lower third positions of the crop, as well as yield components, 1000-grain weight, and productivity were measured. In the upper third, the adjuvant Protect® presented the lowest relative dispersion, resulting in greater droplet spectrum homogeneity. In the middle third, the application with the adjuvant LI700® promoted greater effectiveness, and the application without adjuvants provided a greater number of droplets in the lower third of the crop. In the middle and lower position, the adjuvant Protect® presented a low-quality application, manifested by the lower number of droplets, applied volume, and droplet density. There was no significant difference in yield components resulting from the adverse weather conditions during the experiment. The addition of adjuvants showed greater application efficiency in the upper and middle third of the.